DIFFERENCES IN PROTEASE ACTIVATED RECEPTOR-1 AND THROMBINE LEVELS IN PREECLAMPSIA AND NORMAL PREGNANCY - Gistin Khusnul Khatimah; Joserizal Serudji; Vaulinne Basyir (Universitas Andalas, 2022)
Introduction: Preeclampsia is a condition caused by alterations in endothelial function during pregnancy. Changes in endothelial function result in an increase in coagulation and microvascular fibrin accumulation, which results in impaired placental perfusion. Thrombin, which converts fibrin to fibrinogen, as well as platelet activity, the fibrinolytic system, and anticoagulants, are all procoagulant circumstances in preeclampsia. Thrombin contributes to the pathogenesis of preeclampsia by increasing the expression of sFlt-1 thereby providing an antiangiogenic response. Protease Activated Receptor-1 (PAR-1) is a mediator of thrombin for coagulation and inflammation in preeclampsia. Inhibition of Protease Activated Receptor-1 expression in trophoblasts can enhance placental angiogenesis and vascular remodeling. Recently, only few studies have assessed the levels of Protease Activated Receptor -7 and thrombin in preeclampsia.Objective: To determine the difference in levels of Protease Activated Receptor-1 and thrombin in preeclampsia and normal pregnancyMethods: This study is observational with a cross-sectional comparative study design. Sampling was conducted from March 2020 to March 2021. A total of 66 patients were investigated, with 33 samples of preeclampsia and 33 samples of normal pregnancy. The independent sample T-test was used for statistical analysis.Results: The mean levels of Protease Activated Receptor-1 in the preeclampsia group were higher at 28.56 ± 7.68 ng/mL while normal pregnancy was 21.67 ± 6.92 ng/mL. The results of statistical tests showed that there was a significant difference in levels of Protease Activated Receptor-1 between the preeclampsia and normal pregnancy groups (p<0.05). The mean thrombin level in the preeclampsia group was higher at 72.23 ± 7.99 ng/mL, while in normal pregnancy it was 63.70 ± 8.92 ng/mL. The difference in thrombin levels between the preeclampsia and normal pregnancy groups was statistically significant (p<0.05).Conclusion: Preeclampsia was associated with greater levels of Protease Activated Receptor-1 and thrombin than normal pregnancy. There was a significant difference in the mean levels of Protease Activated Receptor-1 and thrombin between preeclampsia and normal pregnancy.Keywords: Thrombin, Protease Activated Receptor-1(PAR-1), Preeclampsia